2016
DOI: 10.1007/s12639-015-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sodium fluoride toxicity in Schistosoma infected snails: assessment of antioxidants, antiapoptotic, hypoprotein and hypocholesterol activities

Abstract: The snails' tissues represents an intermediate or secondary host for Schistosoma sporocysts where, germ cells within the secondary sporocyst begin to divide to produce thousands of cercariae capable of infecting humans. The aim of the study was to evaluate the toxicity of sodium fluoride in Schistosoma snails' tissue homogenates. A total number of 264 different Schistosoma snails were collected from eight drainage water resources and divided into control uninfected and infected snails; where infected snails di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In another investigation [ 80 ], it was observed that B. alexandrina snails infected with S. mansoni and B. truncatus snails infected with S. haematobium showed a significant elevation in the activities of glutathione reductase (GR), catalase, and superoxide dismutase (SOD). Changes in the infected snail tissue homogenates were also reported [ 81 ]. Upon treatment with sodium fluoride, these altered biochemical parameters were restored to their values in control uninfected snails, indicating the ability of sodium fluoride to inhibit oxidative stress and apoptosis in Schistosoma-infected snails [ 81 ].…”
Section: Discussionmentioning
confidence: 89%
“…In another investigation [ 80 ], it was observed that B. alexandrina snails infected with S. mansoni and B. truncatus snails infected with S. haematobium showed a significant elevation in the activities of glutathione reductase (GR), catalase, and superoxide dismutase (SOD). Changes in the infected snail tissue homogenates were also reported [ 81 ]. Upon treatment with sodium fluoride, these altered biochemical parameters were restored to their values in control uninfected snails, indicating the ability of sodium fluoride to inhibit oxidative stress and apoptosis in Schistosoma-infected snails [ 81 ].…”
Section: Discussionmentioning
confidence: 89%
“…Rizk et al, (2018) reported that B. alexandrina snails infected with S. mansoni and B. truncatus snails infected with S. haematobium demonstrated a high signi cant elevation in glutathione reductase (GR), catalase, and superoxide dismutase (SOD) activities. Changes were also reported in infected snail tissue homogenates(Koriem et al 2016). The mentioned biochemical parameters were restored to their values in control uninfected snails upon treatment with sodium uoride, suggesting its ability to inhibit oxidative stress and apoptosis produced in Schistosoma-infected snails(Koriem et al 2016).…”
mentioning
confidence: 78%
“…Changes were also reported in infected snail tissue homogenates(Koriem et al 2016). The mentioned biochemical parameters were restored to their values in control uninfected snails upon treatment with sodium uoride, suggesting its ability to inhibit oxidative stress and apoptosis produced in Schistosoma-infected snails(Koriem et al 2016). In response to parasitic infection, B. alexandrina and B. truncatus snails increase their defensive haemocytes, which generate large volumes of ROS to damage or kill parasite larvae.Steroid hormones testosterone and estradiol were promoted in Biomphalaria at shedding stage, while in Bulinus, they were suppressed.…”
mentioning
confidence: 78%
“…•− to H 2 O 2 [56] and catalase-like isoform X1 (XP_025098387.1) could further detoxify two H 2 O 2 molecules into H 2 O and O 2 [57]. Similarly, glutathione peroxidase-like (XP_025090868.1) protein can consume reduced glutathione for detoxifying H 2 O 2 and also lipid peroxides generated by lipid peroxidation in Schistosoma-infected snails [57], while peroxiredoxin (XP_025109048.1) reduces H 2 O 2 , lipid hydroperoxides and ONOO − .…”
Section: Protein Profile Of Control Ampullamentioning
confidence: 99%
“…•− to H 2 O 2 [56] and catalase-like isoform X1 (XP_025098387.1) could further detoxify two H 2 O 2 molecules into H 2 O and O 2 [57]. Similarly, glutathione peroxidase-like (XP_025090868.1) protein can consume reduced glutathione for detoxifying H 2 O 2 and also lipid peroxides generated by lipid peroxidation in Schistosoma-infected snails [57], while peroxiredoxin (XP_025109048.1) reduces H 2 O 2 , lipid hydroperoxides and ONOO − . Among the identified enzymes, there were several glutathione-S-transferases (XP_025113955.1; XP_025113405.1; XP_025107274.1), which are known to catalyse the nucleophilic attack of reduced glutathione on electrophilic centres of toxic compounds [56].…”
Section: Protein Profile Of Control Ampullamentioning
confidence: 99%